Perception of Agricultural Students and Agro-professionals towards Agricultural Education and Skill Development in India: Connect and Disconnect - Mahra, Girijesh Singh; Sharma , V.P.; Lenin, V.; Satyapriya,; Sarkar, Sujit (Indian Journal of Extension Education, 2015)
India is entering in phase of demographic dividend. Presently, India has more than 50 per cent of its population within the  age group of 15 to 59 and 28 percent of population in age group of 15-29. Furthermore, by 2020, more than 65 percent of  Indian population will be under working age group. Manpower availability in agricultural sector indicated that more than  12000 agricultural graduates pass out from the state agricultural universities (SAUs) all over the country every year, of  which only 2000 find job in private and public sector, leaving a huge number of graduates unemployed. This agricultural  demographic dividend may become an asset as well as liability for Indian agriculture, depending upon the extent of skill  development among agricultural students. For capturing perception of agricultural students, data has been gathered from  100 agricultural students comprising from State Agricultural Universities, MANAGE and ICAR-IARI. To analyze the  perception of agro-professionals, 25 Kisan Call Centre level- I graduate employees and 25 agro entrepreneur were  interviewed. The present study has analyzed the existing perception of agricultural students and agro-professionals  towards agricultural education and skill development in India. Respondents have shown high importance level towards  core employability skills, professional skills and communication skills however respondents perceived that the  implementation level of core employability skills, professional skills and communication skills in Indian agricultural  education system is low. Skill gap analysis has shown that there is high skill gap in four core employability skills (team  work, entrepreneurship, practical application and self-motivation), three professional skills (creativity, problem solving  ability and statistical competence) and three communication skills (verbal communication, non-verbal communication  and technical writing) and these skills needs to be given more importance in agricultural education system in India.
Keywords: Agricultural education; demographic dividend; skill gap and employability